Kinomic profiling of tumour xenografts derived from patients with non–small cell lung cancer confirms their fidelity and reveals potentially actionable pathways. (February 2021) - Tabbò, Fabrizio; Guerrera, Francesco; van den Berg, Adrienne; Gaudiano, Marcello; Maletta, Francesca; Bessone, Luca; Nottegar, Alessia; Costardi, Lorena; de Wijn, Rik; Ruijtenbeek, Rob; Delsedime, Luisa; Sapino, Anna; et al.
Abstract: Introduction: High fidelity between non–small cell lung cancer (NSCLC) primary tumours and patient-derived tumour xenografts (PDTXs) is of paramount relevance to spur their application. Extensive proteomic and kinomic analysis of these preclinical models are missing and may inform about their functional status, in terms of phosphopeptides and hyperactive signalling pathways. Methods: We investigated tumour xenografts derived from patients with NSCLC to identify hyperactive signalling pathways. Fresh tumour fragments from 81 NSCLC surgical samples were implanted in Nod/Scid/Gamma mice, and engrafted tumours were compared with primary specimens by morphology, immunohistochemistry, gene mutation analyses, and kinase activity profiling. Four different tyrosine and serine/threonine kinase inhibitors were tested against primary tumour and PDTX lysates using the PamGene peptide microarray platform. Results: The engraftment rate was 33%, with successful engraftment being more associated with poor clinical outcomes. Genomic profiles led to the recognition of hotspot mutations, some of which were initially undetected in donor samples. Kinomic analyses showed that characteristics of primary tumours were retained in PDTXs, and tyrosine kinase inhibitors (TKIs) responses of individual PDTX lines were either expected, based on the genetic status, or alternatively defined suitable targets unpredictable by single-genome fingerprints. Conclusions: Collectively, PDTXs mostly resembled their parental NSCLC. Combining genomic and kinomic analyses of tumour xenografts derived from patients with NSCLC, we identified patients' specific targetable pathways, confirming PDTXs as a preclinical tool for biomarker identification and therapeutic algorithm'' improvement. Highlights: Reliable preclinical models are pivotal for successful cancer research. Tumour xenografts derived from patients with non–small cell lung cancer retain main features of their parental tumours. Patient-derived tumour xenografts serve as a platform for patient stratification. Kinomic analyses identify relevant, potentially actionable, targets.